Konsep Penerapan Akad Mudharabah Pada Sistem Operasional Asuransi Syariah - Tito, Luki; Sobarna, Nanang (-, 2025)
This research aims to analyze the concept of mudharabah contract in the operational system of Islamic insurance. The mudharabah contract is one of the main principles in Islamic economics used in the management of funds between the policyholder (shahibul maal) and the insurance company (mudharib). Using the literature study method, this research examines relevant literature on the implementation of the mudharabah contract in Islamic insurance, including the profit-sharing mechanism, the responsibilities of each party, and compliance with Sharia principles. The research results show that the mudharabah contract in Islamic insurance provides a more just and transparent alternative compared to the conventional insurance system. However, the challenges in its implementation include regulatory aspects, transparency in fund management, and protection of policyholders' rights. Therefore, the optimization of the application of mudharabah contracts in Islamic insurance requires synergy between financial institutions, regulatory authorities, and policyholders to ensure compliance with Sharia principles and to enhance public trust in the Islamic financial system.